Proteolysis-Targeting Chimera (PROTAC): Is the Technology Looking at the Treatment of Brain Tumors? - Lospinoso Severini, Ludovica; Bufalieri, Francesca; Infante, Paola; Di Marcotullio, Lucia (Frontiers in Cell and Developmental Biology, 2022)
Post-translational modifications, such as ubiquitylation, need to be tightly controlled to guarantee the accurate localization and activity of proteins. Ubiquitylation is a dynamic process primarily responsible for proteasome-mediated degradation of substrate proteins and crucial for both normal homeostasis and disease. Alterations in ubiquitylation lead to the upregulation of oncoproteins and/or downregulation of tumor suppressors, thus concurring in tumorigenesis. PROteolysis-TArgeting Chimera (PROTAC) is an innovative strategy that takes advantage by the cell’s own Ubiquitin-Proteasome System (UPS). Each PROTAC molecule is composed by a ligand that recruits the target protein of interest (POI), a ligand specific for an E3 ubiquitin ligase enzyme, and a linker that connects these units. Upon binding to the POI, the PROTAC recruits the E3 inducing ubiquitylation-dependent proteasome degradation of the POI. To date, PROTAC technology has entered in clinical trials for several human cancers. Here, we will discuss the advantages and limitations of PROTACs development and safety considerations for their clinical application. Furthermore, we will review the potential of PROTAC strategy as therapeutic option in brain tumor, focusing on glioblastoma.